1993
DOI: 10.1161/01.res.73.2.379
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of K+ currents in isolated human ventricular myocytes from patients with terminal heart failure.

Abstract: Prolongation of the action potential has been postulated to be a major reason for the altered diastolic relaxation of the heart in patients with severe heart failure. To investigate the electrophysiological basis for this action potential prolongation in terminal heart failure, K' currents were recorded in single ventricular myocytes isolated from 16 explanted hearts of patients undergoing transplantation. Results from diseased hearts were compared with ventricular cells isolated from six undiseased donor hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
416
3
8

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 648 publications
(456 citation statements)
references
References 38 publications
29
416
3
8
Order By: Relevance
“…Our electrophysiological data support the possibility that similar alterations occur in the STZ‐hyperglycemic mouse model employed here. Importantly, reduction in the outward K + Kv currents and prolongation of AP duration in mammals appear to be a conserved response to a variety of physio‐ and pathological conditions dictated by an increase in workload of the myocardium, including ischemic cardiomyopathy,60, 61 hypertension,62 pressure overload,63 aging,20, 64 and heart failure 18, 65, 66. Thus, the enhanced beat‐to‐beat variability observed in diabetic myocytes may represent a feature shared with other diseased conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Our electrophysiological data support the possibility that similar alterations occur in the STZ‐hyperglycemic mouse model employed here. Importantly, reduction in the outward K + Kv currents and prolongation of AP duration in mammals appear to be a conserved response to a variety of physio‐ and pathological conditions dictated by an increase in workload of the myocardium, including ischemic cardiomyopathy,60, 61 hypertension,62 pressure overload,63 aging,20, 64 and heart failure 18, 65, 66. Thus, the enhanced beat‐to‐beat variability observed in diabetic myocytes may represent a feature shared with other diseased conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that heart failure originates at the cellular scale [28,29,30]. Alterations in ionic currents and calcium handling lead to a prolonged action potential, a lower …”
Section: Heart Failurementioning
confidence: 99%
“…a'i the lQ~a.J:d t:.ec:tifut:. CJl..t:.-rent, X KI , and the transient outward current, ITO' [5,6]; as well as a decrease in Na/K pump current [7]. It should be pointed out that the clinical relevance of the prolongation of action potential duration is still uncertain, since it has been shown to be present mostly at long, and often unphysiologic, cycle lengths.…”
Section: Electrophysiological Mechanismsmentioning
confidence: 99%